Within the nebula - Hamilton, Edmond, 1904-1977; Rankin, Hugh, 1878-1956 (Salt Lake City, UT : Project Gutenberg, 2024)
"Within the Nebula" by Edmond Hamilton is a science fiction novel originally published in the late 1920s. Set within a vast interstellar universe, the book explores the themes of cosmic danger and the responsibilities of interstellar governance through the perspective of a representative attending the Council of Suns. The narrative unfolds as the Council faces an unprecedented threat from the Orion Nebula, whose accelerating spin threatens to destroy the universe. The story follows the protagonist, who, along with two other representatives$1 (Ba plant-man from Capella and an Arcturian$1 (Bembarks on a crucial mission to investigate the enigmatic forces causing the nebula's impending cataclysm. As they navigate the fiery depths of the nebula, they discover a hidden world at its center inhabited by bizarre, shape-shifting creatures that manipulate the nebula's forces. The trio engages in a desperate struggle for survival as they work to halt the nebula$1 (Bs destructive spin, ultimately revealing the sinister motivations of its inhabitants. The climax centers around their race against time to prevent universal annihilation, blending adventure with deeper reflections on the consequences of technological prowess and survival instinct in the cosmos. (This is an automatically generated summary.)s
Release date is 2024-05-01
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Adventure stories; Nebulae -- Fiction